Development of a colorimetric sensor array for squid spoilage assessment. (15th May 2015) - Zaragozá, Patricia; Fuentes, Ana; Ruiz-Rico, María; Vivancos, José-Luis; Fernández-Segovia, Isabel; Ros-Lis, José V.; Barat, José M.; Martínez-Máñez, Ramón
Highlights: An optoelectronic nose for the shelf-life assessment of squid has been designed. Microbial counts exceeded the acceptability limits on the third day of storage. The optoelectronic nose successfully predicted microbial growth and headspace changes. Squid spoilage could be monitored with the chromogenic dyes array. The optoelectronic nose designed is an excellent tool to assess squid shelf-life. Abstract: The aim of this work was to develop and evaluate a rapid, easy-to-use optoelectronic system for the shelf-life assessment of squid in cold storage. For this purpose, an optoelectronic nose was designed, which consisted of an array containing six sensing materials prepared by combining different dyes and two inorganic supports (aluminium oxide and silica gel). Samples were packaged with the colorimetric array and kept in cold storage for 12 days. Squid spoilage was monitored simultaneously by the colorimetric array and by the physico-chemical and microbial analyses during storage. Samples exceeded the acceptability limits for microbial counts on the third day. PCA analysis carried out with CIELab showed that the colorimetric array was able to discriminate between fresh squid fit for consumption and spoiled squid. The statistical models obtained by PLS, with the optoelectronic nose, successfully predicted CO2 and O2 content in the headspace as well as microbial growth.